2022
DOI: 10.3389/fpsyg.2022.1061529
|View full text |Cite
|
Sign up to set email alerts
|

Teleworking in times of a pandemic: An applied study of industrial companies

Abstract: The purpose of this study is to determine the effect of teleworking on self-reported job satisfaction and workers’ productivity in the context of the COVID-19 pandemic. A survey was administered to 331 teleworkers belonging to industrial companies, whose data were analyzed with a PLS-SEM structural equation model. The results indicate that communication with coworkers, time spent teleworking, and workplace suitability positively affect self-reported productivity, while trust on the part of supervisors and work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…The fact workers of the companies were in the same situation may have promoted greater affect via social support during remote working between workers and supervisors. Similar results were mentioned by Becerra-Astudillo et al (2022), (p. 1). These authors observed that "communication with coworkers, time spent teleworking and workplace suitability positively affect self-reported productivity while trust on the part of the supervisors positively affect job satisfaction.…”
Section: Social Relationships At Worksupporting
confidence: 89%
See 1 more Smart Citation
“…The fact workers of the companies were in the same situation may have promoted greater affect via social support during remote working between workers and supervisors. Similar results were mentioned by Becerra-Astudillo et al (2022), (p. 1). These authors observed that "communication with coworkers, time spent teleworking and workplace suitability positively affect self-reported productivity while trust on the part of the supervisors positively affect job satisfaction.…”
Section: Social Relationships At Worksupporting
confidence: 89%
“…The relationship of family distractions, lifestyle choice, role overload and operational discomfort with life satisfaction, respectively, was sequential and positively mediated by distress and job performance (Kumar et al, 2021). Negative effects of work-family conflict also affect job satisfaction and self-reported productivity, according to Becerra-Astudillo et al (2022).…”
Section: Emotional Demandsmentioning
confidence: 99%
“…In tandem with numerous studies (Barbieri et al, 2021;Ipsen et al, 2021;Lee, 2021;Becerra-Astudillo et al, 2022;Antunes et al, 2023;Demerouti and Bakker, 2023;Kruyen et al, 2023), our study illuminates the enduring impact of job demands, such as increased social isolation, while emphasizing the crucial role of organizational and individual resources in alleviating stress and enhancing job satisfaction. It is also essential to consider the complex interaction between the factors of the JD-R model during crises, like the COVID-19 pandemic, as elucidated by Demerouti and Bakker (2023).…”
Section: Discussion Of the Findingssupporting
confidence: 66%
“…For many, WFH proved particularly difficult owing to the lack of equipment, performancerelated limitations, and lower social support from colleagues and managers (Ipsen et al, 2021;Lee, 2021). These factors coupled with a lack of organizational support can lead to reduced wellbeing and productivity among workers (Ipsen et al, 2021;Becerra-Astudillo et al, 2022;Mihalache and Mihalache, 2022).…”
Section: Psychosocial Risk Factors and Working From Homementioning
confidence: 99%
See 1 more Smart Citation